Effect of Bryophyllum pinnatum Aqueous Leave Extract on Some Biochemical and Hematological Parameters in Albino Rats - Ibrahim, Toma; Jennifer Watti, Ezekiel; Mohammed Mafio, Bintu; Liki Barnabas, Clifford; Faruk Ahmad, Umar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study assessed how Bryophyllum pinnatum (Crassulaceae) leaf extract in water affected the biochemical and hematological parameters of albino rats. Five groups of twenty rats were created: a control group and four treatment groups that received extract at doses of 50, 100, 200, and 400 mg/kg body weight. Alkaloids, flavonoids, tannins, phenols, saponins, steroids, and proteins were all detected by phytochemical analysis; the greatest concentration of phenols was 9.6 ± 0.005 mg/100g, while the lowest was 0.29 ± 0.005 mg/100g. When compared to the control, hematological markers such as hemoglobin, red blood cells (RBC), white blood cells (WBC), and packed cell volume (PCV) did not significantly change. Biochemical examination revealed no discernible alterations in bilirubin, alkaline phosphatase (ALP), or alanine transaminase (ALT). The treated groups did, however, see a dose-dependent drop in albumin and an increase in aspartate transaminase (AST). According to the results, Bryophyllum pinnatum has no toxicological effects on hematological parameters, although elevated AST and decreased albumin may cause mild liver damage at higher dosages. It is advised to conduct more research with larger dosages and longer treatment durations, concentrating on other factors.